Strategies for structural modelling of CLT panels under cyclic loading conditions. (1st November 2019) - Franco, Luca; Pozza, Luca; Saetta, Anna; Savoia, Marco; Talledo, Diego
Highlights: Analysis and interpretation of the experimental results of campaign carried out on wall system within SOFIE project. Analysis of CLT-wall systems by means of component-level models. Comparison of global and local response using numerical and experimental results. Evaluation of out-of-plane displacement effect of connections on the response of CLT-wall systems. Abstract: Cross Laminated Timber (CLT) is an extensively used technology to build medium- and high-rise buildings, especially thanks to the rapidity of execution, environmental sustainability, and good mechanical performances. Since this material is presently employed also in seismic-prone areas, the assessment of numerical modelling strategies to reproduce the cyclic behavior of CLT-wall systems has become a relevant research topic within the structural engineering field. Two different modelling approaches can be adopted to model the seismic behavior of such systems: the phenomenological approach and the component-level one. After a comparative presentation of the two approaches, the paper focuses on the different strategies used to create reliable component-level models able to reproduce the CLT panel-connection system behavior both at the global and local level (i.e., in terms of force-displacement curve and cumulative energy, as well as uplift and slip displacements). The experimental tests carried out at CNR-IVALSA during the SOFIE project – after a preliminary phase of interpretation of the experimental dataset, necessary to identify the peculiarities of the test procedures – are used as a comparative basis to assess the quality of the numerical results. The obtained outcomes demonstrate that the component-level approach could be a feasible and reliable method to reproduce the CLT panel connection systems cyclic behavior, also at a local level, provided that the behavior of each individual component is properly calibrated.